2017
DOI: 10.1111/arcm.12287
|View full text |Cite
|
Sign up to set email alerts
|

On the Metal‐Leaf Decorations of Post‐Byzantine Greek Icons

Abstract: Metal leaves were widely used as decorative materials in post-Byzantine ritual painting. Fiftytwo icons (mid-15th to mid-19th centuries) were studied by means of analytical techniques in order to reveal the materials and techniques encountered in their metal-leaf decorations. High-purity gold leaf was used throughout the studied period. Silver was employed rarely and mostly during the latter part of the period in consideration, while metal powders were mostly used from the mid-18th century onwards. The identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 28 publications
0
28
0
Order By: Relevance
“…The National Art Gallery of London [9] provides an average thickness of medieval gold leaf of around 2.69 µm based on the calculation with the given weight of the orin and the number of leaves per coin, which seems signi cantly thicker than the historical records, indicating the presence of diverse speci cations for medieval gold leaf. Indeed, scienti c analysis of artefacts has shown that the thickness of medieval gold leaf varies from 100 nm to a few microns [6,12,13]. It is interesting to note that while each of these estimates describes the produced gold leaf as having a very regular square or rectangular shape (in agreement with observations), there is no mention of the offcuts necessarily produced from trimming the leaf edges and so the thickness estimates provided above should be considered as an upper bound.…”
Section: Introductionmentioning
confidence: 74%
“…The National Art Gallery of London [9] provides an average thickness of medieval gold leaf of around 2.69 µm based on the calculation with the given weight of the orin and the number of leaves per coin, which seems signi cantly thicker than the historical records, indicating the presence of diverse speci cations for medieval gold leaf. Indeed, scienti c analysis of artefacts has shown that the thickness of medieval gold leaf varies from 100 nm to a few microns [6,12,13]. It is interesting to note that while each of these estimates describes the produced gold leaf as having a very regular square or rectangular shape (in agreement with observations), there is no mention of the offcuts necessarily produced from trimming the leaf edges and so the thickness estimates provided above should be considered as an upper bound.…”
Section: Introductionmentioning
confidence: 74%
“…Simply speaking, gilding is the process to attach metal leaves or foils onto a surface of other materials; water gilding (also called bole gilding) and oil gilding (or mordant gilding) are the most common types of traditional gilding techniques. In water gilding, metal leaf is laid atop a "bole", which mainly contains ne clay and is usually bound with proteinaceous media; a high-gloss surface can be realized through a thorough surface burnishing [10]. In oil gilding, siccative oil-based binding media are employed, and the metal leaf laid above is unburnishable and the surface hence appears relatively matte [10].…”
Section: Gilding Techniques and Stratigraphymentioning
confidence: 99%
“…In water gilding, metal leaf is laid atop a "bole", which mainly contains ne clay and is usually bound with proteinaceous media; a high-gloss surface can be realized through a thorough surface burnishing [10]. In oil gilding, siccative oil-based binding media are employed, and the metal leaf laid above is unburnishable and the surface hence appears relatively matte [10]. Due to the high metal gloss caused by the surface burnishing, water gilding is also called "glossy gilding" [9].…”
Section: Gilding Techniques and Stratigraphymentioning
confidence: 99%
“…Simply speaking, gilding is the process to attach metal leaves or foils onto a surface of other materials; water gilding (also called bole gilding) and oil gilding (or mordant gilding 1 ) are the most common types of traditional gilding techniques. In water gilding, metal leaf is laid atop a "bole", which mainly contains ne clay and is usually bound with proteinaceous media; a high-gloss surface can be realized through a thorough surface burnishing [9,10]. In oil gilding, siccative oil-based binding media are employed, and the metal leaf laid above is unburnishable and the surface hence appears relatively matte [10].…”
Section: Gilding Techniques and Stratigraphymentioning
confidence: 99%